PENGARUH LITERASI KEUANGAN, KEMISKINAN DAN GAYA HIDUP TERHADAP PINJAMAN KONSUMSI DENGAN KEBUTUHAN EKONOMI SEBAGAI VARIABEL MODERASI (STUDI PADA MASYARAKAT JAKARTA SELATAN) - Mamangung Ronrong, Elvin; Gos Ishak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of financial literacy, poverty level, and lifestyle on individuals’ decisions to use consumer loans, as well as to investigate the role of economic needs as a moderating variable. The research is motivated by the growing phenomenon of consumer loan usage amid low levels of financial literacy and increasing economic pressure in society. A quantitative approach with an explanatory method was employed in this study. Data were collected through questionnaires distributed to 200 productive-age respondents residing in South Jakarta who have experience using consumer loan services. The data were analyzed using SmartPLS 4.0 with the Partial Least Square–Structural Equation Modeling (PLS-SEM) technique. The results reveal that financial literacy, poverty level, and lifestyle significantly influence consumer loan decisions. Moreover, economic needs were found to significantly moderate the relationship between the independent variables and consumer loans. These findings indicate that individuals with low financial literacy, under economic pressure, and with a consumptive lifestyle tend to be more inclined to utilize consumer loans as a solution to urgent financial needs.